2011
DOI: 10.1016/j.econedurev.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of student aid on the duration of study

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Similar results were obtained by Glocker (2011), who focused on two aspects: the duration of the students' career and the probability of actually graduating with a degree. Applying a discrete-time duration model on German university students from 1984 to 2007, she found that students who obtained aid actually experienced lower dropout, but did not graduate faster.…”
Section: Literature Reviewsupporting
confidence: 70%
“…Similar results were obtained by Glocker (2011), who focused on two aspects: the duration of the students' career and the probability of actually graduating with a degree. Applying a discrete-time duration model on German university students from 1984 to 2007, she found that students who obtained aid actually experienced lower dropout, but did not graduate faster.…”
Section: Literature Reviewsupporting
confidence: 70%
“…Students with fellowships and research assistantships have higher completion rates and shorter time-to-degree than students with teaching assistantships, tuition waivers, or those who support themselves (Ehrenberg and Mavros, 1995;Siegfried and Stock, 2006). This was also observed in Germany even when parental or private transfers and student aid recipients were awarded the same amount of financial aid (Glocker, 2011).…”
Section: Financial Considerationsmentioning
confidence: 78%
“…High-intensity work during studying is observed to slow academic progression in the United States (US) (Darolia, 2014), Italy (Triventi, 2014), France (Body et al, 2014), the United Kingdom (UK) (Jewell, 2014) and Finland (Häkkinen and Uusitalo, 2003). By contrast, student aid reforms that increased conditional financial aid in Germany (Glocker, 2011) and in Norway (Gunnes et al, 2013) enhanced on-time graduation.…”
Section: Other Labour-market Outcomesmentioning
confidence: 99%